Are cellulose nanofibrils safe for biomedical applications? - Vilar, Madalena (2019)
Nanomedicine is based on the application of nanotechnologies into the medical field to advance and improve diagnostics, prevention and treatment of human disease. While its expansion has been enormous in the last years, its progress must go hand in hand with nanosafety, i.e., with the safety evaluation of nanomaterials in an early phase of its development or application into a product. Cellulose appears as a natural and readily available material, which fits within the supply-demand chain: ecological, abundant and low cost. Particularly, cellulose nanofibrils (CNF) show great mechanical strength and high water-uptake capability and have the ability to form translucent structures with high elasticity and selective permeability, which make them attractive e.g., as constituents of surgical dressings and membranes for bone regeneration. Bacterial nanocellulose is already being used, but CNF produced from plants are also finding potential to be applied in tissue engineering and regenerative medicine. However, CNF may bring more toxicological concerns than the bacterial type, due to impurities associated with the chemical and mechanical processes used to produce them or due to their different physicochemical properties that may underlie unforeseen biological effects. The main objective of this work was to evaluate the safety of two different CNFs, through the analysis of their cytotoxic, genotoxic and epigenetic effects in human osteoblasts. The CNFs were obtained from the same raw material – industrial bleached Eucalyptus globulus kraft pulp - by two different methods: TEMPO-mediated oxidation and enzymatic hydrolisis. The physicochemical properties of the CNF gels obtained, including fibrillation yield, degree of polymerization and size were evaluated. The CNF cytotoxicity was assessed by the MTT assay and the genotoxicity by the cytokinesis-block micronucleus assay; their epigenetic effects were evaluated through gene expression analysis of the DNA methytransferases genes, DNMT1 and DMNT3b, responsible for the cellular methylation pattern, using qRT-PCR. The results obtained for the several endpoints were integrated in order to contribute to the characterization of the potential toxic effects of these new CNF in an early phase of their lifecycle. This knowledge will be relevant to decide whether these CNF may be further developed for applications in the nanomedicine field, or shall be modified to give rise to safer CNF.